Geometry Strength of Honeycomb Sandwich Panel - Mohd Amin, Norliyati; Maskor, Siti Nor Fatykha; Joohari, Ilya; Jamadin, Adiza (International Journal of Integrated Engineering, 2019)
The geometry strength of honeycomb sandwich panel with several types of core were investigated.Â Â There are four types of sandwich panels; Rectangular Core Sandwich Panel (RCSP), Horizontal Core Sandwich Panel (HCSP), Triangular Core Sandwich Panel (TCSP) and Symmetrical Core Sandwich Panel (SCSP). For all types of panel, the upper and bottom layers and the inner core made from the plywood with different thickness. The performance of the honeycomb sandwich panel subjected to four-point bending test and punching shear test were investigated. The results of flexural test showed that RCSP that having the rectangular core has the highest maximum load of 9.79 kN compared to HCSP and TCSP. The maximum load of RCSP in the punching shear test achieved 34.35 kN which was higher than SCSP. Â All the specimens having the core shear failure.